Middle Income Trap in the World, Reasons for Turkey's Being Caught in the Middle Income Trap and Recommendations for Exit - Akyıldız, Songül (Fırat University, 2022)
The Turkish economy, which is at the middle-income level, rose to the lower-middle income group in 1955 and was in this group for 50 years. The Turkish economy, which has developed in many ways over the years, a break occurred in 2005 and when it was analyzed in terms of per capita income, it was seen that it rose to the upper middle-income level. Especially after this increase, it has been a matter of debate whether Turkey can reach the per capita income level of high-income countries. When examined over the years, the slowdown in the growth performance of the Turkish economy after 2012, depending on the developments in the world economy, caused the problems in the direction of the middle-income trap to be among the current issues. Therefore, it is of great importance for the Turkish economy how achieved this success the countries that rose to the high-income group without being caught in the middle-income trap and the countries that rose from the upper-middle-income group to the high-income group. In this context, whether the Turkish economy is at risk of middle-income trap will be examined in the light of some social and economic data and some strategies will be explained to avoid to avoid middle income trap risk will be explained.

Orta gelir seviyesinde yer alan Türkiye ekonomisi, 1955 yılında alt-orta gelir grubuna yükselmiş ve 50 yıl boyunca bu grupta yer almıştır. Yıllar içinde birçok yönden gelişme gösteren Türkiye ekonomisinde 2005 yılında bir kırılma meydana gelmiş ve kişi başı gelir açısından incelendiğinde üst orta gelir seviyesine yükseldiği görülmüştür. Özellikle bu yükselme sonrasında Türkiye’nin yüksek gelirli ülkelerin kişi başı gelir düzeyine ulaşıp ulaşamayacağı tartışma konusu olmuştur. Yıllar itibariyle incelendiğinde dünya ekonomisindeki gelişmelere bağlı olarak 2012 yılından sonra Türkiye ekonomisinde büyüme performansının yavaşlamaya başlaması, orta gelir tuzağı yönündeki problemlerin güncel konular arasında yer almasına neden olmuştur. Dolayısıyla orta gelir tuzağına yakalanmadan yüksek gelirli ülkeler grubuna yükselen ülkeler ile üst-orta gelir grubundan yüksek gelirli ülkeler grubuna yükselen ülkelerin bu başarıyı nasıl sağladıkları, Türkiye ekonomisi açısından büyük önem taşımaktadır. Bu bağlamda Türkiye ekonomisinin orta gelir tuzağı riski altında olup olmadığı bir takım sosyal ve ekonomik veriler ışığında incelenecek, orta gelir tuzağı riskinden sakınmak için bazı stratejiler açıklanacaktır.
DÜNYADA ORTA GELİR TUZAĞI, TÜRKİYE’NİN ORTA GELİR TUZAĞINA YAKALANMA NEDENLERİ VE ÇIKIŞI İÇİN ÖNERİLER